1923
DOI: 10.1017/s0031182000014876
|View full text |Cite
|
Sign up to set email alerts
|

Some Strongylata

Abstract: The bursate nematodes here described have been obtained from three sources: (a) Dr F. W. O'Connor permitted me to deal with his valuable collection from Samoa and the Ellice and Gilbert Islands; (b) Sir Arthur Keith and Mr Burne allowed me to collect and examine certain Strongylata parasitising a gorilla whose body had been placed at the disposal of the College of Surgeons, and to compare them with Cobbold's type material from the ostrich; I am much indebted to these gentlemen for their aid; (c) my own Indian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

1925
1925
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 3 publications
0
5
0
2
Order By: Relevance
“…The genus Paralibyostrongylus is already known in the gorilla, since the species P. hebrenicutus was originally described in this host (Lane, 1923). Puylaert (1967) has shown that in reality the species is a parasite of rodents of the genus Atherurus which is a "transfuge" parasite in the gorilla (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Paralibyostrongylus is already known in the gorilla, since the species P. hebrenicutus was originally described in this host (Lane, 1923). Puylaert (1967) has shown that in reality the species is a parasite of rodents of the genus Atherurus which is a "transfuge" parasite in the gorilla (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Parmi les Nipostrongylinae, seul le cycle de Nippostrongylus brasiliensis (Travassos, 1914) [ = Nippostrongylus muris (Yokogawa, 1922) Lane, 1923, a fait l'objet de très nombreux travaux.…”
Section: Discussionunclassified
“…2, A à G) : nous ne donnons que quel ques figures, le matériel correspondant à la redescription de Paralibyostrongylus hebrenicutus (Lane, 1923) donnée par Puylaert, 1967.…”
Section: -Description Des Adultesunclassified